Reviving Indigenous Handloom Traditions: Exploring the Role of Missing Women Entrepreneurs in Sustainable Rural Development in Dhemaji, Assam - Adak, Rina; Singha, Seema S. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The purpose of this study is to examine higher secondary school teachers’ perceptions of smart classroom teaching and its impact on students’ learning outcomes. The “Adhunik Siksha Yojna” initiative by the Department of Higher Education, Arunachal Pradesh, aims to enhance the quality of the teaching-learning process through the integration of smart classroom technologies. A descriptive survey method was employed using a self-designed questionnaire, and data were collected from a randomly selected sample of 30 teachers from six higher secondary schools across three districts: Changlang, Longding and Namsai. The findings reveal that over 90% of the classrooms are not yet adequately equipped to be considered smart classrooms. However, there has been noticeable progress in the number of smart classrooms compared to the previous year. Although many classrooms still require substantial upgrades, the implementation of the “Adhunik Siksha Yojna” provides optimism that the transformation to smart classrooms across the region will be achieved in the near future.